Addition of oral fexofenadine to topical therapy leads to a significantly greater reduction in the serum interleukin‐31 levels in mild to moderate paediatric atopic dermatitis. (1st April 2022) - Ningombam, A.; Handa, S.; Srivastava, N.; Mahajan, R.; De, D.
Summary: Background: Recent evidence has suggested that oral antihistamines could have a beneficial role in atopic dermatitis (AD) because of their anti‐inflammatory action. Aim: To evaluate the effectiveness of adding an oral second‐generation, nonsedating, H1‐receptor antihistamine (fexofenadine) to topical treatment in AD. Methods: In this prospective randomized study, 50 patients with a diagnosis of mild to moderate AD were recruited and randomized into two groups: Group A was given appropriate topical treatment (topical tacrolimus 0.03–0.1% ointment once daily along with topical fluticasone propionate 0.05% cream once daily, as well as paraffin‐based emollients) combined with oral fexofenadine, while Group B was given appropriate topical treatment only. Both groups received the respective treatments for 8 weeks. Results: There was no significant difference between the two groups in terms of the SCORing Atopic Dermatitis and the 5‐dimensions Itch Scale at any of the time points (Weeks 2, 4 and 8). However, in the fexofenadine group, the level of serum interleukin (IL)‐31 decreased significantly from baseline to Week 8 of treatment. Conclusions: Although we could not conclusively confirm the clinical efficacy of adding oral fexofenadine to topical treatment in AD, serological evaluation indicates that fexofenadine treatment can lead to significant lowering of serum IL‐31 levels in patients with AD. Abstract : Recent evidence has suggested that oral antihistamines could have a beneficial role in atopic dermatitis (AD) due to their anti‐inflammatory action. The observations in the present study indicate that fexofenadine treatment can lead to significant lowering of levels of serum interleukin‐31, the major cytokine mediating itch, in patients with AD.